2016
DOI: 10.1016/j.canep.2016.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory analysis of ERCC2 DNA methylation in survival among pediatric medulloblastoma patients

Abstract: Aim Medulloblastoma is the most frequent malignant pediatric brain tumor. While survival rates have improved due to multimodal treatment including cisplatin-based chemotherapy, there are few prognostic factors for adverse treatment outcomes. Notably, genes involved in the nucleotide excision repair pathway, including ERCC2, have been implicated in cisplatin sensitivity in other cancers. Therefore, this study evaluated the role of ERCC2 DNA methylation profiles on pediatric medulloblastoma survival. Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Furthermore, there were 9341 (2.99%) CpG probes with even lower maximum value than that of cg05293407 TRIM27 indicating its narrow range was reasonable. Meanwhile, plenty of studies have revealed that aberrant DNA methylations of these hypo-methylated CpG probes were also involved in diseases (e.g., female panic disorder risk associated cg07308824 HECA and paediatric medulloblastoma prognosis associated cg02257300 ERCC2 ) [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there were 9341 (2.99%) CpG probes with even lower maximum value than that of cg05293407 TRIM27 indicating its narrow range was reasonable. Meanwhile, plenty of studies have revealed that aberrant DNA methylations of these hypo-methylated CpG probes were also involved in diseases (e.g., female panic disorder risk associated cg07308824 HECA and paediatric medulloblastoma prognosis associated cg02257300 ERCC2 ) [48,49].…”
Section: Discussionmentioning
confidence: 99%